Para que serve um sistema de avaliação externa do ensino? a visão dos coordenadores pedagógicos de um município no interior paulista - Silva, Maria Nazaré da (2020)
The increasing number of municipal education networks that choose to implement their own external large-scale evaluation system has drawn Brazilian researchers' attention to the possibilities of the pedagogical use of their results in the school environment. This research aims to investigate if the implementation of such a system leads the schools to construct a culture that appropriates its results and how this impacts the work of the pedagogical coordinators (PC), leading them to promote improvements in school practices. The target was to study this process in two schools belonging to a county in the North of Greater São Paulo. Using a qualitative research approach, we opted for semi-structured interviews and documental analysis for data collection. The subjects were two PC, working in school units with different characteristics. They were able to inform if and how they used the external evaluation results to guide their work of promoting professional development to teachers, investing in their continuous education. The analysis and discussion of the data were carried out in light of the theoretical contributions that deal with external evaluation, considering its potentialities and limits. We observed that, through collaborative work, which begins at the municipal education department and ends at the school units, there was the construction of a culture that uses the results of external evaluation, manifesting itself positively in the work of the two participants. Both of them said that the results of the external evaluation contribute to their task of planning, implementing, and monitoring the educational process taking place in their schools. According to the PCs, the results of external evaluation, combined with those attained from different assessment instruments, open up positive possibilities for their work with teachers. The research also showed some aspects that require attention: the use of the results of the external evaluation to pay bonuses for the teachers and the frequency with which these evaluations occur since it is difficult to overcome the pupils' identified problems in the short period between the testing. Considering the limitations imposed on this investigation, we believe that these two points deserve further and more in-depth study. Other researchers should go deeper into exploring these critical features of Brazilian schools, in order to improve the quality of the education offered to its population